Eksistensi Majalah IBER Bahasa Sunda sebagai Media Dakwah Persatuan Islam (1970-1974) - Hariri Jabal Syukur (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to describe the history of the establishment and content of Islamic studies in Iber Magazine as a media for Persis da'wah in Bandung City in 1970-1974. The research method used is the historical research method which consists of four stages, namely heuristics, criticism, interpretation, and historiography. The results showed that K.H.E. Abdullah initiated the establishment of the Sundanese language Iber Magazine in August 1967 under the auspices of the Bandung City Persis Branch. Iber Magazine edition No. 33 October 1970 to No. 84 December 1974 presents varied Islamic studies content ranging from aqidah, sharia, and tasawwuf. The conclusion of this research is that Iber Magazine has succeeded in presenting da'wah that is interesting and easily understood by the people of Bandung, the majority of whom speak Sundanese. Iber Magazine also carries a mission to invite Muslims to return to the pure teachings based on the Qur'an and As-Sunnah. This approach not only aims to educate, but also to make a real contribution in building a clearer, more relevant and contextual understanding of Islam in the midst of changing times. Keywords: Bandung City, Iber Magazine, Islamic Da'wah, Persatuan Islam, Sundanese Language.